A legal research on the adequacy of the anti-trafficking in persons and Anti-Smuggling of Migrants Act 2007 in providing the remedies to victims of trafficking / Norhaslinda Abd Rahman - Abd Rahman, Norhaslinda (2018)
Human trafficking is a complex global crime that exploits women, men and children. Due to the seriousness of the crime, the law of Anti-Trafficking in Persons and Anti- Smuggling of Migrants Act has been enacted in 2007. Despite the enactment of the law, the victim is still struggling in getting their compensation. It is compulsory for the provisions to provide the compensation to victims in order to reflect the heinous nature of the offence. Hence, the study attempts to provide an understanding of remedies law in the Act by comparing the remedies provision in Malaysian law and United States Law. The study adopts qualitative research methodology which involves doctrinal research and semi structured interview. The target population of the study is government enforcement agencies who are involved in enforcing the Act, the public prosecutor who is involved in prosecuting the cases and the Protection Officer in shelter home, who are protecting the victims. There is a gap in the Act on providing the compensation to victims of trafficking. Hence, this study contributes to the body of knowledge on human trafficking and the body work on implementation research. This study indicates the needs to improve the compensation provision that obviously violates the rights of the victims.